Sensitivity and Specifity of Anorectal Manometry to Diagnose Hirschsprung Disease in Children with Chronic Constipation - علي وجيه; الشهابي زهير; ابراهيم علي; عبدو آراس (Latakia University Journal -Medical Sciences Series, 2021)
Aim of study: evaluating the role of anorectal manometry in diagnosing Hirschsprung Disease to reduce reliance on rectal biopsy procedure. Methods: during years 2019-2020 a prospective study conducted on 49 children suffering from chronic constipation with one or more of these characteristics (abdominal distention– history of delaying meconium– enema depend– hard stool– pain bowel movements), as these patients underwent the test, depending on presence or absence of rectoanal inhibitory reflex, patients underwent conservative treatment or rectal biopsy procedure. Results: Reflex was present in 40 patients. Rectal biopsies of 9 patients who were negative reflex were normal in 3, aganglionec in 6. Sensitivity, specificity, positive predictive value, negative predictive value of manometry test were 100%, 66%, 93%, 100% respectively. Conclusion: ARM is an effective and safe tool. With high sensitivity and negative predictive value of manometry test, there is no need for rectal biopsy when test is normal.